Pediatric Patient With Ulcerative Colitis-Associated Bronchiectasis. Issue 4 (7th April 2020) - Russi, Abigail; Gurbani, Neepa; Rosen, Michael J.; Mallon, Daniel; LeBlanc, Francis R.
ABSTRACT: We report a unique case of ulcerative colitis-associated bronchiectasis in a pediatric patient 6 years after colectomy. The patient presented with a chronic cough and had a computed tomography demonstrating bronchiectasis. She was treated with sputum expectoration (airway clearance) via chest physiotherapy and pulse-dose steroids with a prolonged oral taper. Her initial response was excellent; however, she experienced a recurrence of symptoms with de-escalation of airway clearance. Pulmonary extraintestinal manifestations of inflammatory bowel disease are most often diagnosed later in life. Both the severity of this patient's presentation and her age are unique to this case.